Environmental Studies and Environmental Laboratory Testing in Accordance to ISO Standards - R Desrina (Testing Center for Oil and Gas LEMIGAS, 2011)
ISO’s standards have been applied not only by the manufacturing industries but also universities as well as research institutions. Three ISO standards are commonly applied: ISO 9001, ISO 17025, and ISO 14001. Although these three standards have differences in the purpose, criteria, and emphasis, these standards can be applied side-by-side by an organization. Eventhough, many questions arise when the organization undertake more than one ISO. These questions, for examples, are: Is it not enough possessing just one ISO, for example ISO 9000 series only? What is the relation between one ISO to another? What is the relation between ISO and the existing regulations? Following the ISO system there is an internal affair in the institution that maintains and manages the quality system according to ISO, for example ISO 14000, environmental management standards. On the other hand, there is a research group in the institution that performs technical services for environmental laboratory testing and environmental research and studies. What are actually the difference functions between these two activities? This paper tries to conduct study in order to give answers for those particular questions. This paper is neither intended for describing ISO in details nor for tutorial purposes. Either comprehensive training or implementing ISO is conducted by a special authorized agency.